1986
DOI: 10.1093/infdis/154.6.930
|View full text |Cite
|
Sign up to set email alerts
|

Iontophoresis of Vidarabine Monophosphate for Herpes Orolabialis

Abstract: The cutaneous application of antiviral agents was studied by iontophoresis, a process that increases penetration of most drugs 20- to 60-fold. Twenty-seven subjects with vesicular orolabial herpes were treated one time in a double-blind, placebo-controlled clinical study: nine received vidarabine monophosphate (ara-AMP), nine received acyclovir (ACV), and nine received NaCl. Ara-AMP-treated lesions yielded lower titers of virus after 24 hr compared with lesions treated with NaCl or ACV (P less than .05). Ara-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…We believe the delivery method used by us, i.e. iontophoresis, accounts for the observed effectiveness of Ara-AMP (29), but no differences between ACV and placebo were found after iontophoresis. Lack of effectiveness of ACV iontophoresis may be related to a high solution pH of 10.6 obtained on dissolving ACV powder.…”
Section: Treatment Of Herpes Simplex Cutaneous and Orolabial Infectionsmentioning
confidence: 79%
See 1 more Smart Citation
“…We believe the delivery method used by us, i.e. iontophoresis, accounts for the observed effectiveness of Ara-AMP (29), but no differences between ACV and placebo were found after iontophoresis. Lack of effectiveness of ACV iontophoresis may be related to a high solution pH of 10.6 obtained on dissolving ACV powder.…”
Section: Treatment Of Herpes Simplex Cutaneous and Orolabial Infectionsmentioning
confidence: 79%
“…The animal studies described above provided a rationale for antiviral iontophoresis; thus we proceeded to perform a double-blind, placebocontrolled clinical trial in human volunteers (29). An IND protocol was approved by FDA for studying Ara-AMP and ACV.…”
Section: Treatment Of Herpes Simplex Cutaneous and Orolabial Infectionsmentioning
confidence: 99%
“…Harris (6) , em seguida, descreveu as primeiras aplicações da iontoforese na medicina, utilizando a técnica para o transporte das seguintes substâncias: sulfato de cobre para o tratamento de tinea pedis e cervicite crônica, sulfato de zinco para o tratamento de otite crônica e rinite vasomotora, nitrato de prata para o tratamento de osteoartrite e artrite reumatóide. A iontoforese também foi utilizada no transporte de pilocarpina transcutânea em pacientes com fibrose cística (7) , de corticosteróides para o tratamento de condições músculo-esqueléticas e urológicas (8) , de anestésicos locais na membrana timpânica e na mucosa periodontal (9)(10) , de fluoreto de sódio para redução da sensibilidade dental (11) , de monofosfato de vidarabina para o tratamento de Herpes simplex (12) e de gentamicina no controle de queimaduras auriculares (13) .…”
Section: Introductionunclassified
“…Iontopho- resis has also been called iontherapy or electroosmosis. Iontophoresis has a long history of being used to enhance penetration of charged molecules through the skin [9][10][11][12][13][14]. More specifically, recent in vitro studies have demonstrated increased transdermal transport of acyclovir with iontophoresis [15][16][17], although those investigations used clinically impractical treatments of 30 min to 7 h of iontophoresis.…”
mentioning
confidence: 99%